ECONOMIC CONTEXT OF VOLUNTEERING AND LABOUR MARKET IN SPORT - Caslavova, Eva; Kraft, Jiri; Voracek, Josef; Bartova, Monika (Ekonomika, 2014)
Abstract. Volunteering for society is of multidimensional significance nowadays. From the organisation’s position, it represents a cheap source of work, mostly in the fields where there are several reasons for the work not being done by professionals, or possibly where it saves time for the employees who can more intensively perform other activities. It is of economical significance not only in the calculation of costs and expenses in the non-profit organizations’ management, but also on the macro-economical level. Therefore, several countries perform conversions of volunteering into full-time jobs, possibly into the economic value of volunteering in the respective country’s GDP creation. The problem probably lies in the fact that the acquired data depend more on the volunteering evaluation and are hardly comparable among the respective countries.From the marketing point of view, the other significance is found in creating goodwill and its spread by the organizations dealing with volunteering that can be used in systematic work with the media, in acquiring new volunteers, and in creating new types of stimuli for them.This research deals with the commitment and motivations of the young generation of Czech students of the Faculty of Physical Education and Sport of the Charles University in Prague (further FTVS UK) and of the following foreign universities and independent graduate schools: West Virginia State University (further WVSU) in the United States of America, and Deutsche Sporthochschule Köln (further DSHS) in the Federal Republic of Germany. The acquired results show that Czech students engage in volunteering very little in comparison with the foreign ones. Czech students have even stated that they do not have sufficient motivation for volunteering. If they engage, then it is mainly in the field of sports, which is quite understandable in the case of students of sports branches of study. Actually, over 85% of FTVS UK students only volunteer in the sports domains occasionally or very seldom, and they usually do it at sport events. At the same time, foreign German and U.S. students volunteer in sport clubs as a regular activity, also more students volunteer than in the Czech Republic. From the institutional point of view, sport clubs appear to be the most important promoter of volunteering in all of the mentioned countries.For students of the studied universities, the main reason for becoming a volunteer is “to acquire new experiences”. Another reason is the fact that they want to “support a good idea / project”. The research has shown that American students consider volunteering to be a moral obligation. In fact, volunteering in their society is a completely ordinary thing which makes citizens to be proud. For American students, to be serviceable to other people is the most important factor. This can be justified by the fact that volunteering is so popular in the USA because it is accepted as an ordinary part of life. On the contrary, German students prefer the fun standpoint connected with volunteering when performing volunteering. At the same time, Czech students give priority to an interesting environment to volunteer in. In general, regarding the respondents’ motivations we can state that students of these three universities evaluate volunteering as being a very good experience for them, and they mostly want to keep on doing it. However, this motivation was lower for the FTVS UK students in absence of any reward for their work. This implies that the Czech students perceive the essence of volunteering differently from foreign students.Key words: volunteering, volunteering in sport, benefits of volunteering for NGOs in sport, volunteers’ motivations, stimuli and motivating factors for volunteering